Procesul de gentrificare a spaţiilor de locuit urbane. Concept şi explicaţii alternative - Nițulescu, Dana Cornelia (Calitatea Vieții, 2006)
In this paper I intend to define and show the main explanatory theories of the gentrification process, in the context of some large tendencies in the urban sociology. Synthetically, the phenomenon depicts the transformation of an aged urban area into a middle class neighbourhood and the dislocation of the old resident population. The main distinction I took into account and which, in a way, organises the present paper was that the process has special features in terms of cultural area in which it shows up: in Anglo-saxon cultural space, gentrification is a consequence of the capital economy and the consumption patterns, while in the former socialist countries, area gentrifcation is more a primitive action to get capital, not an effect of having economic resources.